The difference in C7 to wall distance in a group of software developers with and without moderate chronic neck pain. - Kovac, Dimitrije; Krkeljas, Zarko (Work, 2025)
Background: As the prevalence of non-traumatic neck pain (NTNP) increases, particularly among computer workers, identifying contributing factors is essential for developing preventative strategies. Objective: This study investigates the association between c7-to-wall distance and chronic NTNP in software developers, a population characterized by prolonged sedentary behavior and high computer usage. Methods: The study employed the C7-to-wall distance (C7WD) test, recognized for its reliability and ease of use, to measure the kyphotic curve as an indicator of spinal posture. Ninety software developers (age = 35.3 ± 5.4 yrs; male = 56, female = 34;) with an average working experience of 9.2 ± 4.5 yrs as a full-time software developer (40.7 ± 1.8 h/week) were examined for postural pathologies and allocated to two groups based on presence of neck pain. Results: The key finding was a significant correlation between increased C7WD and the presence of moderate chronic NTNP in software developers, revealing that those with neck pain tended to have a greater C7WD. It was observed that all participants exhibited mild kyphotic posture irrespective of pain presence. Conclusion: The results suggest that although a relationship exists, the clinical significance of the difference in C7WD between those with and without chronic NTNP is debatable. The findings emphasize the need for further comprehensive research that encapsulates biomechanical, functional, and psychosocial factors to holistically understand and manage NTNP in the software developer population.